Analyzing the Development of the Vannamei Shrimp Industry in Bengkalis Regency Using Porter’s Five Forces Approach - Rosa, Nageeta Tara; Perdana, M. Alkadri; Rahayu, Sri (Jurnal EMT KITA, 2026)
This study aims to analyze the development of the vannamei shrimp industry in Bengkalis Regency using Porter’s Five Forces approach. The research employed a qualitative descriptive method through interviews, field observations, and document analysis involving shrimp farmers, government agencies, and fisheries-related business actors. The results indicate that the development of the vannamei shrimp industry in Bengkalis Regency is influenced by a relatively strong competitive industry structure. The bargaining power of suppliers and buyers is high, while the intensity of competition among industry players is also considerable. Meanwhile, the threat of new entrants and substitute products is at a moderate level. These findings suggest that although the vannamei shrimp industry in Bengkalis Regency has significant economic potential, strengthening competitiveness through integrated and sustainable strategies is essential to ensure optimal industry development.